Evidence for an unusual transmembrane configuration of AGG3, a class C Gγ subunit of Arabidopsis. (22nd December 2014) - Wolfenstetter, Susanne; Chakravorty, David; Kula, Ryan; Urano, Daisuke; Trusov, Yuri; Sheahan, Michael B.; McCurdy, David W.; Assmann, Sarah M.; Jones, Alan M.; Botella, José R.
Summary Heterotrimeric G proteins are crucial for the perception of external signals and subsequent signal transduction in animal and plant cells. In both model systems, the complex comprises one Gα, one Gβ, and one Gγ subunit. However, in addition to the canonical Gγ subunits (class A), plants also possess two unusual, plant‐specific classes of Gγ subunits (classes B and C) that have not yet been found in animals. These include Gγ subunits lacking the C–terminal CaaX motif (class B), which is important for membrane anchoring of the protein; the presence of such subunits gives rise to a flexible sub‐population of Gβ/γ heterodimers that are not necessarily restricted to the plasma membrane. Plants also contain class C Gγ subunits, which are twice the size of canonical Gγ subunits, with a predicted transmembrane domain and a large cysteine‐rich extracellular C–terminus. However, neither the presence of the transmembrane domain nor the membrane topology have been unequivocally demonstrated. Here, we provide compelling evidence that AGG3, a class C Gγ subunit of Arabidopsis, contains a functional transmembrane domain, which is sufficient but not essential for plasma membrane localization, and that the cysteine‐rich C–terminus is extracellular.